Formation of the phenotype “epilepsy–autism” in childhood - A. I. Kudlatch; D. A. Kot; L. V. Shalkevich (Русский журнал детской неврологии)
The combination of autistic spectrum disorders (ASD) with epilepsy is one of the most common neuropsychiatric comorbidities, which occurs with a frequency of up to 46 %. Such a high frequency is explained by the similarity of the pathophysiological mechanisms of each of the nosologies development. The common basis for both epileptogenesis and the development of ASD is the anomalies of neural communication mediated by the inversion of neurotransmission. In the formation of the epilepsy–autism phenotype the most significant is impairment of the departments responsible for the verbal-mediated social functioning. Such disorders are manifested in the lag of mental functions development, as well as in the epileptiform activity forming and epileptic seizures triggering. The epilepsy – autism comorbid phenotype core is represented by forms with an established genetic defect associated with structural pathology of the CNS. However, other ways of forming such a phenotype are also possible. Thus, in the epileptic or epileptiform encephalopathies picture there are often symptoms of ASD called an acquired epileptic neuropsychological syndrome. On the other hand, ASD (or the pervasive developmental disorder semiotics) may develop against the epileptiform changes background. In such cases, autistic epileptiform (in case of clinical seizures–epileptic) regression is diagnosed. Our concept of the epilepsy–autism phenotype forming is based on a detailed comparison of the etiology and pathogenesis of epilepsy and ASD. It is presented in the original cyclic sequence form. The variability of the epilepsy–autism phenotype is also presented in the form of the diagram explaining the perspective of each of the nosologies relationship.